Pengaruh Campuran Thinner Terhadap Daya Rekat dan Ketebalan Lapisan Hasil dari Alat Custom Refill Cat Semprot - Ahmad Lubi; Yunita Sari; Rani Anggarainy; Ardi Candra Fatkhurrohman; Mohammad Rizqi Dwi Febrianto; Reynaldi Ramadhan; Ferry Budhi Susetyo (Fakultas Teknik Universitas Pancasila, 2023)
A custom spray coating refill equipment has been designed and fabrication. For this reason, it is necessary to trial the equipment that has been made. This study aims to determine the performance of custom spray coating refill equipment. For a comparison parameter, coating and thinner mixture variations were conducted to determine the adhesion and thickness of the coating layer formed. The coating used in this experiment was Nitrocellulose (NC) and Polyurethane (PU) thinner. The ratio of coating and thinner mixture used are 1:1.5, 1:2, and 1:2.5. After mixing, the mixture was put into the sprayer using custom spray paint refill equipment. The mixture of coating and thinner was sprayed onto the SPCC steel plate. To measure, the adhesion and thickness of the coating layers, a cross-cut tool (according to ASTM-D3359) and a thickness gauge (according to the ASTM-AMT15) were carried out respectively. It seems the spray paint refill equipment was functioning properly. This is due to the quality of the coating layers having good adhesion, shown by all specimens getting 5B classification (0% not peeled off). Moreover, an increase in the thinner composition is lead to a decrease in the coating thickness.